Factors related to betel chewing among junior high school students in Taiwan - Ho CS, Gee MJ, Tsai CC, Lo CI, Hwang MN: (Blackwell Synergy, 2000)
A cross-sectional study was conducted to explore the betel-chewing behavior of junior high school students in Taichung County in 1998. The sample consisted of 2244 students in the general area and 84 students in the aboriginal area. Fifty percent of the students in the aboriginal area had had the experience of chewing betel, and this figure includes 30.1% of the habitual chewers. The prevalence of habitual betel chewers among the students in the general area is 4.3% to Key words: betel chewing; junior high school 5.0%. The major source of betel quid is friends or classmates, and curiosity ac- students; oral health counts for most students’ first experience of betel chewing.